Extreme Environment Streptomyces: Potential Sources for New Antibacterial and Anticancer Drug Leads? - Periyasamy Sivalingam; Kui Hong; John Pote; Kandasamy Prabakar (International Journal of Microbiology)
Antimicrobial resistance (AR) is recognized as one of the greatest threats to public health and in global concern. Consequently, the increased morbidity and mortality, which are associated with multidrug resistance bacteria, urgently require the discovery of novel and more efficient drugs. Conversely, cancer is a growing complex human disease that demands new drugs with no or fewer side effects. Most of the drugs currently used in the health care systems were of Streptomyces origin or their synthetic forms. Natural product researches from Streptomyces have been genuinely spectacular over the recent years from extreme environments. It is because of technical advances in isolation, fermentation, spectroscopy, and genomic studies which led to the efficient recovering of Streptomyces and their new chemical compounds with distinct activities. Expanding the use of the last line of antibiotics and demand for new drugs will continue to play an essential role for the potent Streptomyces from previously unexplored environmental sources. In this context, deep-sea, desert, cryo, and volcanic environments have proven to be a unique habitat of more extreme, and of their adaptation to extreme living, environments attribute to novel antibiotics. Extreme Streptomyces have been an excellent source of a new class of compounds which include alkaloids, angucycline, macrolide, and peptides. This review covers novel drug leads with antibacterial and cytotoxic activities isolated from deep-sea, desert, cryo, and volcanic environment Streptomyces from 2009 to 2019. The structure and chemical classes of the compounds, their relevant bioactivities, and the sources of organisms are presented.